Categorisation of visualisation methods to support the design of Human-Computer Interaction Systems. (July 2016) - Li, Katie; Tiwari, Ashutosh; Alcock, Jeffrey; Bermell-Garcia, Pablo
Abstract: During the design of Human-Computer Interaction (HCI) systems, the creation of visual artefacts forms an important part of design. On one hand producing a visual artefact has a number of advantages: it helps designers to externalise their thought and acts as a common language between different stakeholders. On the other hand, if an inappropriate visualisation method is employed it could hinder the design process. To support the design of HCI systems, this paper reviews the categorisation of visualisation methods used in HCI. A keyword search is conducted to identify a) current HCI design methods, b) approaches of selecting these methods. The resulting design methods are filtered to create a list of just visualisation methods. These are then categorised using the approaches identified in (b). As a result 23 HCI visualisation methods are identified and categorised in 5 selection approaches ( The Recipient, Primary Purpose, Visual Archetype, Interaction Type, and The Design Process ). Highlights: Established an inventory of 23 Human-Computer Interaction (HCI) visualisation methods. Identified 5 selection approaches. Presented and provided evidence of how the visualisation methods are categorised in each selection approach. Discussed the limitations and benefits of each selection approach.